Intravitreal bevacizumab (avastin) in central retinal vein occlusion - Hsu, Jason; Kaiser, Richard S; Sivalingam, Arunan; Abraham, Prema; Fineman, Mitchell S; Samuel, Michael A; Vander, James F; Regillo, Carl D; Ho, Allen C (Retina (Philadelphia, Pa.), 2007)
To describe the effects of intravitreal bevacizumab in eyes with macular edema resulting from central retinal vein occlusions (CRVO). Retrospective consecutive case series of patients diagnosed with macular edema from CRVO who received intravitreal bevacizumab. Thirty eyes of 29 patients with an average age of 72 years (range, 54-87 years) had intravitreal bevacizumab injections. Mean follow-up was 18.1 weeks. Initial mean visual acuity was 20/394. At the 1- and 2-month follow-up, mean visual acuity improved to 20/237 (n = 26, P = 0.04) and 20/187 (n = 21, P = 0.008), respectively. At the 3- and 4-month follow-up, visual acuity improved from 20/228 to 20/157 (n = 15, P = 0.05) and from 20/313 to 20/213 (n = 11, P = 0.03), respectively. No significant changes in visual acuity were found after 4 months though the number of patients in this group was small. Duration of treatment effect following an injection appears to be limited to 2 months for most patients. No ocular or systemic adverse reactions were noted. The visual benefits of intravitreal bevacizumab for macular edema due to CRVO are apparent early but are not sustained without repeated injections. Larger clinical studies with long-term follow-up will be necessary to better elicit the best regimen for this therapy.